PENGARUH JUMLAH TENAGA KERJA, TINGKAT PENDIDIKAN DAN JUMLAH PENGANGGURAN TERHADAP PERTUMBUHAN EKONOMI KABUPATEN MAGELANG TAHUN 1996-2017 - Heni Wahyu Widayati; Lorentino Togar Laut; Rian Destiningsih (Universitas Tidar, 2019)
Economic growth is one measure in determining people's welfare. One of the economic problems that occur in Magelang Regency is unemployment. The number of unemployed people in Magelang Regency still cannot be reduced, this brings various challenges for local governments in overcoming the number of unemployed. The purpose of this study is to find out the effect of the number of workers, education level and number of unemployed on economic growth in Magelang Regency in 1996-2017. The data analysis method that the researcher used in this study was multiple linear regression analysis with OLS (Ordinary Least Square) model. The collected data is secondary data, the technique of collecting data uses document studies obtained from the Central Statistics Agency (BPS) in the period 1996-2017. The variable number of labor has a significant effect on the economic growth of Magelang Regency in 1996-2017. While the education level variable and the number of unemployed did not significantly influence the economic growth of Magelang Regency in 1996-2017. In this study the results obtained that the overall independent variables consisting of the number of workers, education level and number of unemployed simultaneously have a significant effect on the value of economic growth in Magelang Regency in 1996-2017.